(untitled) (Dhaka University Journal of Biological Sciences, 2016)
The purpose of this study was to adapt Stirling Children’s Well-Being Scale (SCWBS) for measuring well-being of children of Bangladesh. Data were collected from 238 students, ages between 10 to 16 years of three different schools of Dhaka city. Psychometric properties were measured through Cronbach’s alpha (0.746), split-half (0.782), test-retest (0.791), which were satisfactory, respectively at 0.05, 0.05, and 0.01 level of significance. The demonstration of construct validity with Beck Self-Concept Inventory for Youth (BSCI-Y) and Beck Anxiety Inventory for Youth (BAI-Y) (two subtests of Adapted Bangla Beck Youth Inventories of Emotional and Social Impairment Scale) were 0.668 and –0.350, respectively, and item-total correlation (0.258 to 0.451) was also satisfactory. Thus psychometric results support that Bangla SCWBS is suitable for use in Bangladesh context. Mental health professionals can use Bangla SCWBS as a useful tool to assess changes in children’s wellbeing from a positive psychological perspective. Dhaka Univ. J. Biol. Sci. 25(2): 161-167, 2016 (July)